KEUANGAN PUBLIK DALAM PERSPEKTIF EKONOMI ISLAM - arfah, tina arfah (JURNAL ISLAMIKA, 2020)
In a country based on capitalism we will find many problems in the country's economy . This is due to the management of State finances both in terms of income The state and state expenditures are not as expected by the community, there are still many elements of fraud, corruption, etc.. financial management like this will result in an economic crisis and create misery for the community. to overcome this problem the government must use an economic concept that can overcome this problem., The concept that can be applied by the government is public finance in an Islamic economic perspective. Islamic economic concepts have been proven to improve justice and welfare in society.